The Mind Anchor: Peran Trait Rumination dalam Struktur Pengalaman Afektif - Shaleha, Rinanda Rizky Amalia; Yusainy, Cleoputri Al; Herani, Ika (Universitas Brawijaya, 2018)
This study aimed to investigate whether trait rumination has a role in individual’s structure of current affect, specifically on valence and arousal dimension. Within-subject experiment design was used as a study design which involved eighty-one undergraduate students of Department of Psychology, Universitas Brawijaya as participants. Images from International Affective Picture System (IAPS) were used to evoke participant’s affect and measured by Self Assessment Manikin’s (SAM) rating while trait rumination was measured using Ruminative Response Scale (RRS). Statistical analysis using one-way repeated measures ANOVA technique found that trait rumination has a significant role in participant’s structure of current affect on relation between valence stimulus and rating valence (F=5.276, p<0.01) but has no role on relation between arousal stimulus and rating arousal (F=0.753, p>0.05).Penelitian ini bertujuan untuk mengetahui apakah trait rumination memiliki peran dalam struktur pengalaman afektif individu, yaitu dimensi valence dan arousal. Penelitian ini menggunakan desain within-subject experiment dengan melibatkan delapan puluh satu orang mahasiswa baru Prodi Psikologi Universitas Brawijaya sebagai partisipan. Afek partisipan dibangkitkan menggunakan stimulus gambar dari International Affective Picture System (IAPS) yang diukur melalui Self Assessment Manikin (SAM) dan trait rumination diukur menggunakan Ruminative Response Scale (RRS). Hasil analisis statistik menggunakan teknik one-way repeated measures ANOVA menunjukkan bahwa trait rumination memiliki peran signifikan dalam hubungan antara valence stimulus dan rating valence (F=5.276, p<0.01). Namun, trait rumination tidak memiliki peran dalam hubungan antara arousal stimulus dan rating arousal (F=0.753, p>0.05).